Actualization of Religious Moderation Value towards Moderate Attitude of Plandi Village Community, Wonosari District, Malang: Case Study of Weton Calculation in Marriage - Nafiadi, Fardan Haris; Putri, Fitria Azizah Yona; Anggraini, Reni Dwi; Rasmuin, Rasmuin (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Indonesia is known as a multicultural nation because of the diversity of cultures, races, religions, and ethnicities within it. This diversity becomes a special and harmonious thing when one can accept it with an open mind. However, it can be a boomerang if the thought of diversity cannot be accepted and leans to focus on its own culture, race, religion, or ethnicity without seeing the differences implied in the surrounding life. Leaning on one's own thoughts without seeing and trying to know others can cause division and even hostility. Diversity that was originally special because of the peacefulness of differences becomes a place to debate and blame each other because there is no sense of acceptance. Often religious differences become a matter of endless debate as well as cultures that are often alluded to far from religious values are also debated and blamed for each other's beliefs. Therefore, religious moderation comes as a middle way to lead someone to think moderately or can be called neutral thinking. Where moderation teaches to practice the teachings of their religion in a good way, not radical and not extreme. The purpose of this research is to provide an overview of the moderate attitude of the people of Plandi Village, Wonosari District, as the social environment of Plandi Village is still strong in culture and religion. So that this research will describe how the community's belief in existing culture, especially the weton culture and how the impact occurs on cultural beliefs when the value of religious moderation has entered people's lives. This research uses a qualitative approach with interview techniques. The results of this study are the community's belief in the weton calculation culture in marriage and the impact of the actualization of religious moderation values on community attitudes in the calculation culture.